Analysis of perceptions of primary school students towards science using the pictures they draw İlkokul öğrencilerinin fen bilgisine yönelik algılarının çizdikleri resimlerle analizi - Ballıel Ünal, Buket (Journal of Human Sciences, 2017)
This study was conducted with the purpose of analyzing and interpreting the perceptions of 4th grade primary school students studying in the province of Muğla towards science, using the pictures they draw. The study was implemented in the school year of 2015-2016 with 41 4th grade students from the classes A-B at the Toki Ş. J. Yb. Alim Yılmaz Primary School in the province of Muğla. The pictures drawn by the participating students were analyzed semantically and the method of content analysis was used. The study analyzed and interpreted how the students perceived the concept of “Science”, the content they employed in the pictures they drew, whether they were able to establish a connection between Science and their lives, and whether there were differences between male and female students in terms of the content of the pictures they drew. Collaboration was made with three science and technology teachers and two image experts in the analysis. Separate coding lists were formed for each case for the analysis of the qualitative data and the data were coded. In the light of the findings obtained, it was found that 73.6% of male students drew an experiment environment within the theme of laboratory, while 90.9% of the female students did so. It was found that a large proportion of male and female students were influenced by the subjects “our sensory organs”, “technological developments”, “our body and systems”, “classifying matter” and “pollution”, which are included in the curricula. It was concluded that most male and female students perceive the concept of science only in terms of experiments, while this ratio is higher for female students who drew more detailed and colorful environments; they did not think of science outside school and laboratory environments; the connection they established between their lives and science did not exceed the public’s attitude towards this issue, visual stimulants in their surroundings, and what was taught and shown to them by educational institutions; the number of students who used themes other than the drawings and subjects in the textbook was very low; and their levels to relate science and technology class information to daily life were low. Extended English abstract is in the end of PDF (TURKISH) file. Özet Bu araştırma, Muğla ilinde öğrenim gören ilkokul 4. Sınıf öğrencilerinin Fen Bilgisine yönelik algılarının çizdikleri resimlerle analiz edilerek yorumlanması amacı ile yapılmıştır. Araştırmanın uygulaması 2015-2016 eğitim-öğretim yılında Muğla ili Toki Ş.J. Yb. Âlim Yılmaz İlkokulunda 4. sınıf A-B şubelerinde öğrenim gören 41 öğrenci ile gerçekleştirilmiştir. Çalışmaya katılan öğrencilerin çizdikleri resimler anlamsal açıdan incelenmiş ve içerik analizi yöntemi kullanılmıştır. Öğrencilerin “Fen Bilgisi” kavramını nasıl algıladıkları, çizdikleri resimlerde hangi içeriklere yer verdikleri, Fen Bilgisi ve yaşadıkları hayat arasında bağlantı kurup kuramadıkları ve kız ve erkek öğrencilerin çizdikleri resim içeriklerinde farklılıklar olup olmadığı analiz edilmiş ve yorumlanmıştır. Değerlendirme yapılırken üç fen ve teknoloji öğretmeni ve iki resim uzmanı ile çalışılmıştır. Nitel verilerin analizinde her bir durum için ayrı ayrı kodlama listesi çıkarılmıştır ve kodlamalar yapılmıştır. Elde edilen bulgular doğrultusunda, erkek öğrencilerin %73,6’sı resimlerinde laboratuvar teması içerisinde deney ortamı resmederken, bu oranın kız öğrencilerde %90,9 olduğu tespit edilmiştir. Kız ve erkek öğrencilerin büyük bir bölümünün müfredat programlarında yer alan “duyu organlarımız”, “teknolojik gelişmeler”, “vücudumuz ve sistemler”, “maddenin sınıflandırılması” ve “çevre kirliliği” konularından etkilendikleri görülmüştür. Kız ve erkek öğrencilerin büyük bir bölümünün fen bilgisi kavramını sadece deney olarak algıladıkları, kız öğrencilerde bu oranın daha yüksek olduğu ve erkek öğrencilere göre daha detay ve renkli ortamlar çizdikleri, fen bilgisini okul ve laboratuvar ortamı dışında düşünmedikleri, yaşamları ve fen bilgisi arasında kurdukları bağın, bu konuda toplum tutumunun, çevrelerindeki görsel uyaranların ve eğitim kurumlarının onlara öğrettikleri ve gösterdiklerinden daha öteye geçemediği, ders kitabında bulunan çizim ve konuların dışında tema işleyen öğrenci sayısının çok az olduğu ve fen ve teknoloji dersi bilgilerini günlük hayatla ilişkilendirme düzeylerinin düşük olduğu tespit edilmiştir.